Emotion dysregulation and internalizing symptoms affect relationships between ADHD symptoms and borderline personality features among male patients with substance use disorders - Cuneyt Evren; Vahap Karabulut; Izgi Alniak; Bilge Evren; Ozlem Helin Carkci; Hanife Yilmaz Cengel; Pelin Ozkara Menekseoglu; Turan Cetin; Muge Bozkurt; Gokhan Umut (Psychiatry and Clinical Psychopharmacology, 2019)
OBJECTIVES: The aim of the present study was to evaluate the relationship of borderline personality features (BPFs) with attention-deficit/hyperactivity disorder (ADHD) symptoms among male patients with substance use disorder (SUD) and to evaluate the impact of emotion dysregulation on this relationship. We also wanted to control the effects of depression and state anxiety. METHOD: Participants included 305 treatment-seeking male patients with SUD. Participants were evaluated by applying the Borderline Personality Inventory (BPI), the Adult ADHD Self-Report Scale (ASRS), the Difficulties in Emotion Regulation Scale (DERS) and the Beck Depression Inventory (BDI), and the Spielberger State-Trait Anxiety Inventory (STAI). RESULTS: Age, duration of education, marital status, employment status, age at first and age at regular substance use did not differ between those with probable borderline personality disorder (BPD) (n = 155, 50.8%) and those without probable BPD (n = 150, 49.2%). Probable ADHD risk was 3.5 times higher among those with probable BPD. Also ADHD, DERS, depression and anxiety scores were higher in this group with probable BPD. Scale scores were mild and moderately correlated with each other. In hierarchical regression analysis severity of ADHD symptoms (particularly hyperactivity/impulsivity [HI] dimension), together with difficulties in emotion regulation (particularly impulse control difficulties), depression and trait anxiety predicted the severity of BPFs. CONCLUSIONS: These findings suggest that the severity of HI symptoms of ADHD is related with the BPFs, while difficulties in emotion regulation, particularly impulse control difficulties, partially mediate this relationship among patients with SUD.